Religion, secularism, and the spiritual paths of Virginia Woolf - Groover, Kristina K (Palgrave Macmillan, 2019)
Religion, Secularism, and the Spiritual Paths of Virginia Woolf offers an expansive interdisciplinary study of spirituality in Virginia Woolf's writing, drawing on theology, psychology, geography, history, gender and sexuality studies, and other critical fields. The essays in this collection interrogate conventional approaches to the spiritual, and to Woolf’s work, while contributing to a larger critical reappraisal of modernism, religion, and secularism. While Woolf’s atheism and her sharp criticism of religion have become critical commonplaces, her sometimes withering critique of religion conflicts with what might well be called a religious sensibility in her work. The essays collected here take up a challenge posed by Woolf herself: how to understand her persistent use of religious language, her representation of deeply mysterious human experiences, and her recurrent questions about life's meaning in light of her disparaging attitude toward religion. These essays argue that Woolf's writing reframes and reclaims the spiritual in alternate forms; she strives to find new language for those numinous experiences that remain after the death of God has been pronounced
9783030325701
Keywords: Aufsatzsammlung; Englische Literatur; B; Twentieth-Century Literature; Literature; Cultural and Media Studies; Einzelne Autoren: Monographien & Biographien; British and Irish Literature; Religiöse Fragen von Sexualität; Geschlecht und Beziehungen; Religion and Gender; Sociology of Religion; Religionssoziologie und -psychologie; Spiritualität; Mystik; Literarische Stoffe; Motive und Themen; Allgemeine und Vergleichende Literaturwissenschaft; Literature; Modern—20th century; British literature; Gender identity—Religious aspects; Spirituality; Literature; religion and literature; secularism; modernist literature; metaphysical; Virginia Woolf; Mrs. Dalloway; To the Lighthouse; spirituality and literature